If you Give Enough Time to that Which Seems Extremely Improbable, It Can Happen! Applications of the Infinite Monkey Theorem in Secondary Classrooms in Line with the Development of Emotional Skills (Global Journal of Science Frontier Research, 2023)
The research article addresses two main topics the concept of giving sufficient time to seemingly improbable events and the applications of the infinite monkey theorem in secondary classrooms in relation to the development of emotional skills First the idea that if enough time is given to something that seems extremely improbable it is possible for that event to occur is highlighted This notion defies common intuition and suggests that the probability of an event may change over time Second the article focuses on applications of the infinite monkey theorem in high school classrooms The infinite monkey theorem is a metaphor that illustrates the idea that given enough opportunities even an extremely difficult task can be completed In this context we examine how this theorem can be applied to secondary education and the development of emotional skills in students Educational strategies that foster perseverance patience and tolerance for failure by providing students with the time and support necessary to overcome seemingly insurmountable challenges are explored These strategies include long-term projects in which students have the opportunity to work on difficult goals for extended periods of time there by cultiv ating emotional resilience and persistence
Keywords: adoles cents; mathematics; topology; innovation; high school